A New Understanding of Terrorism
XVIII, 366 p.
Keywords: Terrorism is a complex phenomenon that cannot be understood through reading of a number of unrelated academic articles or a dry overview of the history of terrorism or the investigative techniques. For A New Understanding of Terrorism, the Editors have chosen a different paradigm. They have selected numerous case studies from actual events that illustrate various typologies of terrorist actions, be it from a separatist, nationalist, lone-wolf individual terrorist, religious fanatics or environmentalist orientation, and they present these cases within the context of following the trajectories of the terrorist activity, the terrorist act itself and, the response to the event from the relevant authorities. Some chapters concentrate on terrorist attacks that actually took place, others speculate about the possibilities of an attack occurring sometime in the future, such as the chapters on the Olympic Games, Aviation or Rail Security. When possibilities rather than a specific event are discussed, the authors of these chapters draw the attention of the reader towards the same direction—the reasoning, the actual event and the response that followed. The thorough analysis of the presented case studies and the applied counter-measures will, hopefully, if not curtail then possibly at least mitigate the operational and ideological strength of terrorist groups or individual actors. A New Understanding of Terrorism will enable the reader to make the connection between the emotional charge inherent in any terrorist activity, the cold-blooded tactics that lead to the terrorist event itself and the pragmatic and very straightforward, but at the same time very simplistically designed, strategic response that has to come from a synergy between academics, military and law enforcement brainstorming design in order to be more effective in the future.